Build a Used Car Export Comprehensive Service Platform Based on Distributed Architecture - Hao, Qi; Chang, Wenbo; Luan, Xudong; Zhang, Fan (International Journal of Global Economics and Management, 2024)
To establish an authoritative comprehensive platform for the export of used cars, this paper proposes the design and implementation of a distributed architecture for a comprehensive service platform for used car exports. Firstly, it centers around export orders to connect the entire business process. Secondly, it builds the platform based on distributed systems, distributed caching, cloud technology, and load balancing technology for used car export services. Lastly, it verifies the system’s performance through metrics such as maximum concurrent users, transaction response time, throughput rate, success rate, and resource utilization. The results indicate that this system can assist used car export enterprises in completing their business operations. The platform, centered around export orders, connects the entire business process, achieving efficient data utilization, collection, and query of documentary evidence, promoting efficient business operations. It supports one-click generation of documents and certificates, and features vehicle-specific query functions, positioning the platform at a leading level in the field of used car exports.